SIRGAS core network stability - Sánchez, L. (2016)
The main objective of SIRGAS (Sistema de Referencia Geocéntrico para las Américas) is to provide an accurate spatial and time-referenced infrastructure as a basis for Earth System research and to support scientific and practical applications based on high-precise positioning. Following this purpose, significant achievements related to the extension, analysis, and maintenance of this reference frame have been reached during the last years. However, there are still unresolved problems hindering the attainment of the best possible precision. In particular, the assimilation of seismic-related deformations and non-lineal station movements is very difficult and its omission considerably reduces the reliability of SIRGAS as a high precision reference frame. To advance in the solution of these inconveniences, this paper presents the first kinematic model of the SIRGAS reference frame computed after the strong earthquake occurred in the Chilean region of Maule in February 2010. This model is based on the combination of weekly free normal equations covering the time span from April 18, 2010 to June 15, 2013. Computed station positions and velocities refer to the IGb08 reference frame (the IGS realisation of the ITRF2008), epoch 2012.0. The averaged rms precision is˙± 1.4 mm horizontally and˙± 2.5 mm vertically for the station positions at the reference epoch, and ± 0.8 mm/year horizontally and ˙± 1.2 mm/year vertically for the constant velocities. Comparisons with reference frames based onmeasurements before the earthquake (like ITRF2008 or former SIRGAS solutions) make evident the strong deformation caused by this earthquake and the necessity of updating accordingly the reference frames in the affected region.